2013
DOI: 10.1002/icd.1815
|View full text |Cite
|
Sign up to set email alerts
|

Analogue Mental Transformations in 3-Year-Olds: Introducing a New Mental Rotation Paradigm Suitable for Young Children

Abstract: Until now, a successful application of the mental rotation paradigm was restricted to children 5 years or older. By contrast, recent findings suggest that even infants can perform mental rotation. Unlike the methods used in infant studies (looking time), our new research paradigm allows for the measurement and interpretation of reaction times. Kindergartners (aged 3–6 years) were presented with a stimulus configuration on a touchscreen and asked to bring a rotated stimulus into an upright position using the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Some researchers have used manipulation tasks to study MR in toddlers between 2 and 5 years of age [3,63,64]. The goal of these tasks was to manually rotate an object into the same orientation as a reference object, to its upright (canonical) position, or so that it would fit through an aperture.…”
Section: Box 1 Distinctive Stimulus Featuresmentioning
confidence: 99%
“…Some researchers have used manipulation tasks to study MR in toddlers between 2 and 5 years of age [3,63,64]. The goal of these tasks was to manually rotate an object into the same orientation as a reference object, to its upright (canonical) position, or so that it would fit through an aperture.…”
Section: Box 1 Distinctive Stimulus Featuresmentioning
confidence: 99%
“…Nevertheless, future studies with new paradigms may resolve this issue. A recent paradigm, for example, suggested that the relation between angle disparity and RT can already be demonstrated in 3‐year‐olds (Krüger, Kaiser, Mahler, Bartels, & Krist, ). Such paradigms should be adapted to examine the potential effects of anatomically possible and impossible stimuli on mental rotation in even younger children.…”
Section: Discussionmentioning
confidence: 99%
“…3-year-olds (Kr€ uger, Kaiser, Mahler, Bartels, & Krist, 2014). Such paradigms should be adapted to examine the potential effects of anatomically possible and impossible stimuli on mental rotation in even younger children.…”
Section: Discussionmentioning
confidence: 99%
“…Further discussion of MR in preschoolers is beyond the scope of this review, but it is notable that no consistent pattern of sex differences in young children's MR has been reported. For example, neither Krüger (2018) nor Krüger et al (2014) observed sex differences in their preschool-aged research participants. However, Levine et al (1999) reported a substantial advantage for male over female 4.5-year-olds on a spatial transformation task, which included both rotation and translation items, and Frick, Hansen, and Newcombe (2013) reported some sex differences as well with 3-year-old participants.…”
Section: Mental Rotation Of 3d Objectsmentioning
confidence: 92%
“…Other studies failed to find evidence for MR in children younger than 5 years old, and claimed that the failure to find MR in preschoolers reflects a true lack of ability, as opposed to difficulties with the test (e.g., inability to understand instructions; Frick, Ferrara, & Newcombe, 2013;Quaiser-Pohl, Rohe, & Amberger, 2010). Other studies, however, have demonstrated that even 3-and 4-year-olds provide evidence of MR in simplified tasks (Frick, Hansen, & Newcombe, 2013;Krüger, 2018;Krüger, Kaiser, Mahler, Bartels, & Krist, 2014;Levine, Huttenlocher, Taylor, & Langrock, 1999).…”
Section: Mental Rotation Of 3d Objectsmentioning
confidence: 99%